Prognostic Role of Diastolic Left Ventricular Mechanical Dyssynchrony by Gated Single Photon Emission Computed Tomography Myocardial Perfusion Imaging in Post-Myocardial Infarction - Ha, Le Ngoc; Trung, Nguyen Thi Thanh; Son, Mai Hong; Chien, Do Van; Paeng, Jin Chun (World Journal of Nuclear Medicine, 2023)
Objective This study is aimed to assess the prognostic value of diastolic left ventricular mechanical dyssynchrony (LVMD) measured by gated-single photon emission computed tomography (GSPECT) myocardial perfusion imaging (MPI) in post-myocardial infarction (MI).Subjects and Methods The study was conducted on 106 post-MI from January 2015 to January 2019. First, the indices of diastolic LVMD phase standard deviation (PSD) and histogram bandwidth (HBW) of post-MI were measured using the Cardiac Emory Toolbox. Subsequently, the post-MI patients were followed up, and the primary endpoint was major adverse cardiac events (MACEs). Finally, the prognostic value of dyssynchrony parameters for MACE was analyzed by the receiver-operating characteristics curve and survival analyses.Results With the cut-off values of 55.5 degrees of PSD, the sensitivity and specificity in prediction of MACE were 75% and 80.8%, with the cut-off values of 174.5 degrees of HBW, the sensitivity and specificity were 75% and 83.3% respectively. There was a significant difference of time to MACE between groups of PSD less than 55.5 degrees and more than 55.5 degrees. PSD, HBW, and left ventricle ejection fraction (LVEF) assessed on GSPECT were significant factors in the prediction of MACE.Conclusion Diastolic LVMD parameters of PSD and HBW derived from GSPECT are significant prognostic factors in predicting MACE in post-MI patients.
Keywords: diastolic; left ventricular mechanical dyssynchrony; GATED SPECT; MPI; post-MI